Twenty-four-Month Outcomes of the Ranibizumab for Edema of the Macula in Diabetes - Protocol 3 with High Dose (READ-3) Study - Sepah, Yasir J; Sadiq, Mohammad Ali; Boyer, David; Callanan, David; Gallemore, Ron; Bennett, Michael; Marcus, Dennis; Halperin, Lawrence; Hassan, Muhammad; Campochiaro, Peter A; Nguyen, Quan Dong; Do, Diana V (Ophthalmology (Rochester, Minn.), 2016)
To compare 2.0 mg ranibizumab (RBZ) injections with 0.5 mg RBZ for eyes with center-involved diabetic macular edema (DME). Randomized, controlled, double-masked (to the dose), interventional, multicenter clinical trial. A total of 152 patients (152 eyes) with DME. Eligible eyes were randomized in a 1:1 ratio to 0.5 mg (n = 77) or 2.0 mg (n = 75) RBZ. Study eyes received 6 monthly mandatory injections followed by as-needed injections until month 24. The primary efficacy end point of the study was mean change in best-corrected visual acuity (BCVA) and central foveal thickness (CFT) at month 6. Secondary outcomes included the mean change in BCVA and CFT at month 24, and incidence and severity of systemic and ocular adverse events through month 24. A total of 152 eyes were randomized in the study. At month 24, the mean improvement from baseline BCVA was +11.06 letters in the 0.5 mg RBZ group (n = 59) and +6.78 letters in the 2.0 mg RBZ group (n = 54) (P = 0.02). The mean numbers of RBZ injections through month 24 were 18.4 and 17.3 in the 0.5 mg and 2.0 mg RBZ groups, respectively (P = 0.08). The mean change in CFT was -192.53 μm in the 0.5 mg RBZ group and -170.64 μm in the 2.0 mg RBZ group (P = 0.41). By month 24, 3 deaths had occurred in the 0.5 mg RBZ group and 3 deaths had occurred in the 2.0 mg RBZ group; 5 of these 6 deaths occurred secondary to cardiovascular causes, and 1 death occurred as the result of severe pneumonia. All 5 patients with a cardiovascular cause of death had a history of coronary heart disease. At month 24, there were significant visual and anatomic improvements in both groups, with subjects in the 0.5 mg RBZ group gaining more vision. Visual and anatomic gains achieved at month 6 were largely maintained through month 24. No new safety events were identified. In this study population, 2.0 mg RBZ does not appear to provide additional benefit over 0.5 mg RBZ.